2021
DOI: 10.9734/jamb/2021/v21i530353
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ascariasis among Children in Makurdi, Benue State, Nigeria

Abstract: This study was conducted to assess the prevalence of ascariasis among children of 1-15 years old in Wadata, Wurukum, Northbank, Fiidi, and Modern market of Makurdi, Benue State, Nigeria. Prevalence of Ascariasis among children was conducted between January to march 2020. A total of 230 stool samples were randomly collected from children of both sexes and analyzed, using formol-ether concentration technique to determine the presence of eggs of Ascaris lumbricoides. Out of the samples analyzed, 64(27.83%) were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
1
Order By: Relevance
“…Chirdan et al [16] evaluated the prevalence of intestinal parasites in children attending Day Care Centers in Jos, Central Nigeria and reported that 57.8% of children aged 0-59 months were infected with intestinal parasites. In our study, the most prevalent intestinal parasite was A. lumbricoides (13.1%); this rate is higher than that reported in a study conducted in a metropolitan city of Bangladesh (1.4% prevalence among pediatric patients) [17] and lower than that reported in a study on ascariasis prevalence conducted among children aged 1-5 years in Makurdi, Benue State, Nigeria (18.75%) [18].…”
contrasting
confidence: 78%
“…Chirdan et al [16] evaluated the prevalence of intestinal parasites in children attending Day Care Centers in Jos, Central Nigeria and reported that 57.8% of children aged 0-59 months were infected with intestinal parasites. In our study, the most prevalent intestinal parasite was A. lumbricoides (13.1%); this rate is higher than that reported in a study conducted in a metropolitan city of Bangladesh (1.4% prevalence among pediatric patients) [17] and lower than that reported in a study on ascariasis prevalence conducted among children aged 1-5 years in Makurdi, Benue State, Nigeria (18.75%) [18].…”
contrasting
confidence: 78%